2003
DOI: 10.1063/1.1636247
|View full text |Cite
|
Sign up to set email alerts
|

Optical excitation of Er ions with 1.5 μm luminescence via the luminescent state in Si nanocrystallites embedded in SiO2 matrices

Abstract: Optical excitation bands have been investigated for Er-doped SiO2 films, including Si nanocrystallites as sensitizers. The Er-doped films with photoluminescence at 1.5 μm were fabricated using a laser ablation technique. It is found that the major continuous portion of the excitation bands for Er ions completely coincides with that of Si nanocrystallites at room temperature. Thus, it has been demonstrated that the second indirect absorption band of Si nanocrystallites can be used for efficient excitation of Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It was concluded that the Er 3+ ions were excited by the energy transfer from Si-nc. This conclusion was verified by the work of Makimura et al [31] who found that the PL intensity of Er 3+ ions is inversely correlated with Si-nc concentration and proposed that the Er 3+ ions are excited via photogenerated singlet excitations in Si-nc.…”
Section: Si Substratesupporting
confidence: 73%
“…It was concluded that the Er 3+ ions were excited by the energy transfer from Si-nc. This conclusion was verified by the work of Makimura et al [31] who found that the PL intensity of Er 3+ ions is inversely correlated with Si-nc concentration and proposed that the Er 3+ ions are excited via photogenerated singlet excitations in Si-nc.…”
Section: Si Substratesupporting
confidence: 73%
“…The sensitization of Er ion emission ͑ = 1.54 m͒ by host materials, such as crystalline Si ͑c-Si͒, 1,2 amorphous Si ͑a-Si͒, 3,4 and Si nanocrystallites ͑nc-Si͒, [5][6][7][8][9][10][11][12][13][14][15] has been extensively investigated. In the case of c-Si, the nonradiative deexcitation process leads to thermal quenching of Er ion emission.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Among the various hosts, silicon dioxide is commonly selected owing to its large band gap which provides an environment for effective non-radiative energy transfer from a sensitizer to nearby active Er 3þ ions. 12) In recent years a considerable amount of information on both Si nanocrystals [13][14][15] and their sensitization effect on Er photoluminescence (PL) 16,17) has been published. Si nanocluster sensitizers (Si-nc) have been introduced using a variety of techniques.…”
Section: Introductionmentioning
confidence: 99%